A novel dehydrocoenzyme activator combined with a composite microbial agent TY for enhanced bioremediation of crude oil-contaminated soil. (1st April 2023) - Liu, Qiyou; Sun, Shuo; Chen, Shuiquan; Su, Yuhua; Wang, Yaru; Tang, Fang; Zhao, Chaocheng; Li, Lin
Abstract: Bioaugmentation (BA) and biostimulation (BS) synergistic remediation is an effective remediation strategy for oil-contaminated soil. In this study, the optimal combination system of composite microbial agent TY ( Achromobacter : Pseudomona = 2:1) and dehydrocoenzyme activator (NaNO3 (7.0 g/L), (NH4 )2 HPO4 (1.0 g/L), riboflavin (6.0 mg/L)) was screened. Under the best combination system, the degradation rate of crude oil in oil-contaminated soil reached 79.44% after 60 d, which was 1.74 times and 1.23 times higher than that of compound microbial agent TY treatment and dehydrogenase activator treatment, respectively. In addition, a highly efficient combination system was found to target the degradation of oil C10 –C28 fractions by gas chromatography (GC). The increased abundance of dehydrogenase coenzymes such as flavin nucleotides (FAD and FMN), coenzyme I (NAD +, Co I) and coenzyme II (NADP +, Co II) as well as dioxygenases and monooxygenases promote the degradation of crude oil. Furthermore, the dominant genera at the genus level in soil were analyzed by high-throughput sequencing, which were Nocardioides (46.48%–56.07%), Gordonia (11.40%–14.61%), Intrasporangiaceae (5.05%–10.58%), Pseudomonas (1.39%–1.92%) and Dietzia (0.64%–2.77%). Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt) analysis showed that the abundance of genes associated with crude oil degradation such as ABC transporters (2.89%), fatty acid (1.04%), carbon metabolism (4.5%) and aromatic compound (0.92%) was assigned enhanced after 60 d of remediation. These results indicated that the combination system of the compound bacterium TY and the dehydrocoenzyme activator is a propective option for the bioremediation of oil-contaminated soil. Graphical abstract: Image 1 Highlights: A composite microbial agent TY and a novel dehydrocoenzyme activator were used synergistically. Dehydrogenase activators promoted the expression of FAD, NADP +, FMN, NAD + . High-efficiency strategy has targeted degradation of crude oil (C10 –C28 ). The functional gene configuration of ABC transporter, fatty acid and carbon metabolism were enhanced.